The detection of biomarkers in evaporite matrices using a portable Raman instrument under Alpine conditions - Culka, A; Jehlička, J; Vandenabeele, P; Edwards, H G M (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2011)
The detection of relatively low concentrations of the biomarkers in experimentally prepared evaporitic matrices using a portable Raman instrument (Ahura First Defender XL equipped with a 785 nm diode laser and fixed frontal probe) under Alpine conditions was tested. The instrument was able to detect nucleobases thymine (1673 and 984 cm(-1)) and adenine (722 and 536 cm(-1)) at concentrations of 1 wt% in the gypsum matrix outdoors at a low ambient temperature of -10°C and at an altitude of 2860 m(Pitztal, Austria). Amino acids glycine (1324 and 892 cm(-1)) and alanine (1357 and 851 cm(-1)) were unambiguously detected at 10 wt%. The main Raman features: strong, medium and partially weak intensity bands were observed in good agreement with the reference spectra for individual compounds (with a spectral resolution 7-10 cm(-1)) in the wavenumber range 200-1800 cm(-1). In the qualitative part of the experiment it was established that the portable instrument is able to detect the components in the mixture of three biomarkers (glycine, alanine and mellitic acid) and two evaporitic minerals unambiguously. It also detected the majority of the six similar amino acids in the mixture with gypsum and epsomite evaporitic minerals. The results obtained here demonstrate the possibility of a miniaturised Raman spectrometer to be able to cope with the various exobiologically related tasks that can be expected in the future planetary surface exploration missions. Within the payload designed by ESA and NASA for future missions, Raman spectroscopy will represent a unique research instrument.
Keywords: aminokyseliny; Spectrum Analysis, Raman; Amino Acids; Ramanova spektroskopie; Minerals; nízká teplota; mimozemské prostředí; biologické markery; Calcium Sulfate; síran vápenatý; Altitude; Biomarkers; minerály; Extraterrestrial Environment; Cold Temperature; nadmořská výška